2020
DOI: 10.1002/jmv.26219
|View full text |Cite
|
Sign up to set email alerts
|

Detecting SARS‐CoV‐2 RNA in conjunctival secretions: Is it a valuable diagnostic method of COVID‐19?

Abstract: The main purpose of this study is to evaluate the presence of viral RNA of severe acute respiratory syndrome coronavirus‐2 (SARS‐CoV‐2) in conjunctival swab specimen of coronavirus disease 2019 (COVID‐19) patients with and without conjunctivitis to establish the diagnostic value of reverse transcription‐polymerase chain reaction (RT‐PCR) in each case and to describe its clinical characteristics. A cross‐sectional study was conducted at the Hospital Clinico San Carlos of Madrid, Spain. Thirty‐six subjects from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
63
0
9

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(81 citation statements)
references
References 15 publications
5
63
0
9
Order By: Relevance
“…The possibility that the conjunctiva may be a site of virus replication has been indicated in several reports, in cross-sectional as well as monocentric studies or case reports [16,20,22,24,26,[31][32][33][34], posing an important concern for infection prevention in healthcare workers and the general population, and highlighting the need for eye protection in addition to respiratory protection. Despite the lack of frequent isolation of infectious SARS-CoV-2 from the conjunctiva [26], the eye is thus considered a potential portal of entry and spread for the virus.…”
Section: Discussionmentioning
confidence: 99%
“…The possibility that the conjunctiva may be a site of virus replication has been indicated in several reports, in cross-sectional as well as monocentric studies or case reports [16,20,22,24,26,[31][32][33][34], posing an important concern for infection prevention in healthcare workers and the general population, and highlighting the need for eye protection in addition to respiratory protection. Despite the lack of frequent isolation of infectious SARS-CoV-2 from the conjunctiva [26], the eye is thus considered a potential portal of entry and spread for the virus.…”
Section: Discussionmentioning
confidence: 99%
“…However, several studies suggested that the prevalence of ocular signs and symptoms in COVID-19 patients is relatively low. 9 Two separate metaanalyses on ocular manifestations estimated a pooled prevalence of 5.5% and <4%. 10,11 Another meta-analysis showed that the prevalence of conjunctivitis in 1167 COVID-19 patients was about 1%.…”
Section: Ocular Manifestations Of Covid-19mentioning
confidence: 99%
“…[13][14][15][16] Conjunctivitis may be unilateral or bilateral. 9 Two case reports describe the presence of pseudomembranes among severe cases of conjunctivitis. Salducci et al reported one COVID-19 patient with pseudomembranes of fibrin, inflammatory cells, and enlarged preauricular and submaxillary lymph nodes.…”
Section: Ocular Manifestations Of Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…However, this lower detection rate for conjunctival swabs (with or without overt conjunctivitis) is consistent with previous reports. 6 Thirdly, the relative SARS-CoV-2 viral loads from the URT decreased with time in the 1-2 weeks post-COVID-19 symptom onset, regardless of disease severity. This has been shown elsewhere, 7 though this is not always the case.…”
mentioning
confidence: 93%